Impact of educational attainment and economic globalization on obesity in adult females and males: Empirical evidence from BRICS economies - Sart, Gamze; Bayar, Yilmaz; Danilina, Marina (Frontiers in Public Health, 2023)
Obesity has considerably increased since 1980 and become a global epidemic. Obesity-related health problems and the negative social and economic implications of obesity have led international institutions and countries to combat it. This study investigates the role of educational attainment and economic globalization in the global prevalence of obesity in samples of adult females and males in BRICS economies for 1990–2016 through causality and cointegration tests. The results of the causality tests reveal that educational attainment and economic globalization have a significant influence on obesity in both adult females and males in the short run. Furthermore, cointegration analysis indicates a negative effect of educational attainment on obesity in all BRICS economies in the long run, but the influence of economic globalization on obesity differs among the BRICS economies. Furthermore, the negative influence of educational attainment on obesity is revealed to be relatively higher in females than males.